The Effect of Compensation on Employee Performance at Tuan Rondahaim Hospital Pamatang Raya - Adrian K Tarigan (Enrichment : Journal of Management, 2022)
In this study there are two variables are variables X (Discipline) and Y (Performance). This study aims to examine and analyze the influence ofcompensation for employee work at RSUD Tuan Rondahaim Pamatang Raya. Based on the incidental sample method, the total sample in this study was 62 respondents. In this study using primary data obtained from the distribution of questionnaires. The number of questionnaires distributed as many as 62 copies and which can be returned and processed as many as 62 copies. The method of analysis used in this study is simple linear regression analysis and hypothesis testing (t-test). Amount of t-counts (8.382) > of the amount of t-tables (1.99897) then Ha accepted. Based on these results it can be concluded that the compensation has positive and significant effect on employee's work at RSUD Tuan Rondahaim Pamatang Raya.